2011
DOI: 10.1074/jbc.m110.166157
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Tandem MA-3 Region of Pdcd4 Protein and Characterization of Its Interactions with eIF4A and eIF4G

Abstract: One of the key regulatory points of translation initiation is recruitment of the 43S preinitation complex to the 5′ mRNA cap by the eIF4F complex (eIF4A, eIF4E, and eIF4G). The tumor suppressor protein Pdcd4 has been shown to inhibit cap-dependent translation by interacting tightly with the RNA helicase eIF4A via its tandem MA-3 domains. The NMR studies reported here reveal a fairly extensive and well defined interface between the two MA-3 domains in solution, which appears to be stabilized by a network of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…This protein interacts with eIF4A (25,48,53,55) and negatively controls the helicase activity of eIF4A and cap-dependent translation (37,48,55). Notably, beyond free eIF4A, PDCD4 inhibits the function of eIF4F-bound eIF4A (24,53,55), providing a mechanism by which it may be acting as a suppressor of mRNA translation (48,55). There is also evidence that PDCD4 binds RNA and interacts with eIF4G in vitro (2,48,55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein interacts with eIF4A (25,48,53,55) and negatively controls the helicase activity of eIF4A and cap-dependent translation (37,48,55). Notably, beyond free eIF4A, PDCD4 inhibits the function of eIF4F-bound eIF4A (24,53,55), providing a mechanism by which it may be acting as a suppressor of mRNA translation (48,55). There is also evidence that PDCD4 binds RNA and interacts with eIF4G in vitro (2,48,55).…”
Section: Discussionmentioning
confidence: 99%
“…PDCD4, a tumor suppressor protein for which the human gene is located on chromosome band 10q24 (46), has important regulatory functions in mammalian cells (4,14,24,25,33,54,56). This protein interacts with eIF4A (25,48,53,55) and negatively controls the helicase activity of eIF4A and cap-dependent translation (37,48,55). Notably, beyond free eIF4A, PDCD4 inhibits the function of eIF4F-bound eIF4A (24,53,55), providing a mechanism by which it may be acting as a suppressor of mRNA translation (48,55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a translation regulator, Pdcd4 interacts with the eukaryotic translation initiation factor eIF4A, a RNA helicase that catalyzes the unwinding of mRNA secondary structures in 5 0 -untranslated regions (UTRs) (Yang et al, 2003a(Yang et al, , 2004. Binding of Pdcd4 to eIF4A is mediated by the MA-3 domains, whose structure and complex formation with eIF4A have been analyzed in detail (LaRondeLeBlanc et al, 2007;Waters et al, 2007Waters et al, , 2011Suzuki et al, 2008;Chang et al, 2009;Loh et al, 2009). Because binding of Pdcd4 to eIF4A inhibits the helicase activity of eIF4A (Yang et al, 2003a;Yang et al, 2004), it is believed that Pdcd4 functions as a suppressor of cap-dependent translation of mRNAs with structured 5 0 -UTRs.…”
Section: Introductionmentioning
confidence: 99%
“…Pdcd4 was sufficient to induce apoptosis in T-ALL cells, suggesting that apoptosis of T-ALL cells in which miR-21 expression is downregulated is at least partly caused by derepression of Pdcd4. Recent structural studies on PDCD4 revealed that it inhibits initiation of cap-dependent protein translation by binding to the RNA helicase elongation initiation factor 4A (eIF4A) and the scaffold protein elF4G 65 or by blocking internal ribosomal entry site-mediated translation of the prosurvival genes Bcl-XL and Xiap. 42 Interestingly, our correlative studies on BCL-xL protein levels in murine and human T-ALL cell lines confirms that miR-21 is regulating BCL-xL through the repression of Pdcd4.…”
Section: Dicer1 Is Essential For Notch-driven T-all 999mentioning
confidence: 99%